(untitled) (Journal of Governance and Development (JGD), 2023)
The current refugee’s crises across Africa, Middle East and Asia have captured the world’s attention. Much of the existing discourse has stemmed from developed nations and focused on the economic and humanitarian impacts that these lingering crises had on the developed countries. This study being a deviation from the previous studies, investigate the security impact of Sudanese refugees in the Eastern Chad. This study used literature sourced materials and internet resources to examine the security challenges of Sudanese refugees in Eastern Chad by exploring the existing academic and popular literature around historical and contemporary case studies. This is undertaken with a view to overcome the negative effect of refugees on social and environmental implications, economic implications and violent conflict implications of refugees on the host nation. The study recommends that for peace and stability to be ensure efficient and purposive governance leadership that will protect lives and property should be provided, provision of sufficient infrastructure to ease the discomfort of the refugees, and provision of vocations to provide the refugees with gainful employment that will guarantees provision of sustainable livelihood for the displaced victims. The recommendations issued in the paper is of immense importance to the policy maker and the various stakeholders involved in the management of refugee’s crises in Eastern Chad and beyond.